Gas sensing performance of Ti3C2Tx MXene heterojunction structures in greenhouse environments: a mini review - Zhang, Haoming; Xu, Hongyu; Zeng, Wen; Wang, Zhongchang; Zhou, Qu (Frontiers in Chemistry, 2024)
With the continuous advancement of smart greenhouse technologies, digital and informationbased environmental monitoring has emerged as a focal point of research. The development of highperformance gas sensors is central to achieving this objective. In recent years, MXene materials have been widely applied in the field of gas sensors due to their excellent ion mobility, favorable hydrophilicity, outstanding electronic conductivity, and unique physicochemical properties. Various MXene heterojunction structures have been synthesized for gas detection. This review aims to summarize the current state of research on Ti3C2Tx-based gas sensors, explore methods for synthesizing different morphologies of Ti3C2Tx heterojunction structures, and evaluate the sensing behaviors of these configurations to fully harness their potential for gas monitoring in greenhouse environments. Additionally, an in-depth analysis of the sensing mechanisms associated with Ti3C2Tx heterojunction structures will be provided, offering theoretical support for future investigations. The findings indicate that Ti3C2Tx-based nanomaterials demonstrate considerable promise as high-performance sensors for gas detection in greenhouse settings. This innovative research not only provides new insights into the development of gas sensor technologies but also serves as an important foundation for the digitization of environmental monitoring.